The Suitability Of English Textbook "Bahasa Inggris" With The 2013 Curriculum Of Senior High School Grade Xi. - Kuncorojati, Wahyu; , Drs. Djoko Srijono, M.Hum; , Drs. Sigit Haryanto, M.Hum (2015)
In this research, the writer describes the suitability of English textbook for the eleventh grade of Senior High School entitled BAHASA INGGRIS with the 2013 Curriculum. The type of this research is descriptive research. The objects of this research are the text structure and the language features on every chapter in the textbook. There are 5 chapters in the textbook. In the first chapter, there are 11 materials that focus on the textbook. All of the materials are suitable with the 2013 Curriculum. The second chapter consists of 11 materials and they are suitable with the 2013 Curriculum. In the third chapter, there are 7 suitable materials and one unsuitable material. The fourth chapter, there are 7 materials which are suitable with the 2013 Curriculum and one unsuitable material. The last chapter, there are 8 materials that focus in the textbook and all of them are suitable. The total number of the materials that focus in the textbook are 44 materials. And the total number of the materials focus on the 2013 Curriculum are 46. The result of this research shows that there is 95,6% of the suitability of the BAHASA INGGRIS textbook. Finally, the writer concludes that the criteria of the textbook are Very good. The textbook can be used by the students of the eleventh grade of Senior High School, although there are unsuitable materials in the third and fourth chapter.